Original paperEstimation of oral leukoplakia treatment records in the research of the Department of Maxillofacial and Oral Surgery, Medical University of Gdansk - Starzyńska, Anna; Pawłowska, Anita; Renkielska, Dorota; Michajłowski, Igor; Sobjanek, Michał; Błażewicz, Izabela; Włodarkiewicz, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Oral leukoplakia (OL) is the most common potentially malignant lesion of the oral cavity. Aim: The purpose of the study was clinical and epidemiological analysis of patients with OL diagnosed and treated in the Department of Maxillofacial and Oral Surgery, Medical University of Gdansk, comparison of effectiveness of treatment methods, defining whether van der Waal level of OL influences treatment effectiveness, correlation between localization of OL and treatment effectiveness, and defining the optimal OL therapeutic method. Material and methods : Among 55 911 patients diagnosed and treated in the Department in the years 1999–2009, 204 people with OL were selected (104 women, 100 men, average age: 58.1 years). Treatment and observation period of 6 months was completed by 178 (87.25%) patients. Seventy-four patients were treated with cream containing 0.05% tretinoin. Sixty-three patients underwent cryosurgery, and 41 surgery. Control visits were made in week 2, 4, 6 and 8 and 6 months after completed treatment. Results: Three hundred and twenty lesions of OL were diagnosed. According to van der Waal classification, the largest group of patients was classified into stage I and II. The percentage of totally cured patients was 90.07%. There were no statistic differences in effectiveness between surgical and cryosurgical treatment. Conclusions : Evaluation of OL treatment methods depends on localization of the lesions and its stage of progression. The effectiveness of treatment with locally applied tretinoin is smaller in comparison to surgery and cryosurgery. It allows to reduce the number and size of OL lesions, what makes it possible to reduce the number of ablative procedures.